The Commodification of Sport: Exploring the Nature of the Sports Product. Issue 7 (24th May 2018) - Vamplew, Wray
Abstract: Sport becomes a commodity when either consumers are willing to pay to play or watch it or if it has a potential exchange value rather than merely a use one. Such sports commodities can be classified as player products, spectator products, or associated products. Aspects of the definitions of sports products, including dark products, are discussed as are their characteristics in terms of durability, predictability, and complementarity.